2013
DOI: 10.2478/pjct-2013-0039
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface functional groups of nanosilica on the properties of polyamide 6/SiO2 nanocomposite

Abstract: The present study investigated the effect of the surface functional groups of nanosilica on the interfacial, crystallization, and thermal stability of polyamide 6/SiO 2 (PA6/SiO 2 ) nanocomposite, in which nanosilica was modifi ed in situ with both 3-triethoxysilylpropylamine and 3-methacryloxypropyltrimethoxy silane¬ (KH-550 and KH-570). The FTIR analysis results showed the chemical bonding action between the reacting amino groups of nanosilica and end carboxyl groups of polyamide 6 enhanced with increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Degree of surface coverage with modifying groups was calculated on the basis of elemental analysis results and surface areas using Berendsen and de Golan equation …”
Section: Methodsmentioning
confidence: 99%
“…Degree of surface coverage with modifying groups was calculated on the basis of elemental analysis results and surface areas using Berendsen and de Golan equation …”
Section: Methodsmentioning
confidence: 99%
“…1,2 However, the application of neat PA6 or PA66, two kinds of nylon, has been limited to some special fields due to its relatively low thermal conductivity. Therefore, PA is mostly compounded with other polymers [3][4][5] or rigid particles [6][7][8][9][10][11][12][13] to overcome these limitations. Graphene is an atomically thick, two-dimensional (2D) sheet composed of sp 2 carbon atoms arranged in a honeycomb structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, numerous studies have been reported on the enhancement of mechanical properties of PA-based composites by compounding with micro/nano additives such as montmorillonite [ 5 ], SiO 2 [ 6 ], and carbon-based materials such as carbon black [ 7 ], multi-walled carbon nanotubes [ 8 ], and exfoliated graphite [ 9 ] as well as by blending with other polymers such as high-density polyethylene [ 10 ], and polyphenylene sulfide [ 11 ]. However, high anisotropy and aggregation of carbon nanotubes (CNTs), stacking problems of exfoliated graphite, and brittleness in the presence of carbon black do not meet the requirements in the compounding process.…”
Section: Introductionmentioning
confidence: 99%